Nicotine and cannabis routes of administration and dual use among U.S. young adults who identify as Hispanic, non-Hispanic Black, and non-Hispanic White - Kim Pulvers; Nessa Jamalian; Edleen Suh; Peter Faltaoos; Susan L. Stewart; Elizabeth R. Aston (Preventive Medicine Reports)
Background: Use of cannabis and nicotine is at record levels among young adults, and health consequences vary by route of administration. However, there is a paucity of research characterizing use of both substances, especially among individuals of racial/ethnic minoritized identities. Method: Participants (N = 1,032; age 18–25 years) completed a cross-sectional survey administered through an online panel in 2021 in eight U.S. states where cannabis was legal for both recreational and medical use and eight states where cannabis was not legal for medical or recreational purposes. Sampling was stratified by race/ethnicity (Hispanic, non-Hispanic Black, non-Hispanic White) and gender (male, female). Survey weighting was based on state-level gender and race/ethnicity data in the 2021 U.S. Census Bureau. Results: Over one third (37.9%) of respondents reported current use of both cannabis and tobacco, more than double the proportion using tobacco (12.1%) or cannabis (4.1%) only. Vaporization was the most common method for using nicotine (40.2%). Disposable nicotine vape products were used more than any other method (27.1%). Smoking was the most common route of administration for cannabis (35.7%). Simultaneous use of tobacco and cannabis was common (27.0%) overall and greater among those who identify as non-Hispanic Black than non-Hispanic White. There were few differences in product use by gender or state legality. Discussion: Dual cannabis and tobacco use is prevalent among young adults. Given the dynamic regulatory landscape, continued monitoring of specific cannabis formulations and tobacco products is recommended. Trends in simultaneous use of cannabis and tobacco and associated adverse effects warrant continued assessment.